Development of Heyzine Flipbook on Regulatory System Content Integrated with the Qur'an - Ranti An Nisaa; Ayu Fadila; Rizkia Suciati (Postgraduate, University of Mataram, 2026)
21st-century learning is closely related to technology integrated into learning. Education and learning are expected to be able to apply technology by developing digital technology-based learning media. The national education goals and core competencies in the 2013 curriculum in Indonesia require that every learning must foster Islamic values. This study aims to produce a media flipbook, Heyzine, integrated with the Qur'an on the material of the regulatory system. The development (R&D) is adapted from the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis was conducted by examining students' and teachers' needs for learning media for biology content considered difficult. Design included designing media objects and content. Development included creating learning media using the Heyzine application in flipbook format. Implementation included testing the media on students after validation by experts and revisions. Evaluation was conducted to determine the feasibility of the developed media. Assessment validation was carried out by media experts, material experts, linguists, and Qur'anic commentators using questionnaires. The media that had been validated by experts was then tested on Muslim students in grade 11 science, which was divided into two stages, namely a small scale with 29 students and a large scale with 145 students, using questionnaires and interviews as validated by empiricism. It was found that media experts gave a score of 90%, material experts 86.1%, linguists 94.2%, and Qur'anic commentators 94%. The small-scale trial achieved a score of 85.6%, and the large-scale trial achieved a score of 90.5%. Therefore, the flipbook learning media on the Integrated Al-Quranic Regulatory System was declared highly suitable for use as a learning medium. By producing a flipbook Heyzine integrated with the Al-Quran on the regulatory system content, it is hoped that this technology-based learning will continue to prioritize comprehensive Islamic values ​​in biology learning.